West Kennet Long Barrow
The space within the outer stones contains a semicircular forecourt set back into the mound. Out of this court a passage opens, leading to a multicellular interior. When excavated in 1955, the remains of about 30 burials were found, and the tomb appears to have been in use for at least three centuries.